Are Entrepreneurs More Likely to Be Obese? - Yibing Wang; Xueling Qu; Haitao Wang (Iranian Journal of Public Health, 2021)
Background: Entrepreneurs not only promote a nation’s economic growth but also increase employment. The risk of obesity among entrepreneurs may bring heavy economic burdens not only to the entrepreneurs but also to the national health care system. We aimed to examine the association between entrepreneurship and the risk of obesity.